Pressure-induced structural, magnetic and transport transitions in Sr2FeO3 from first-principles - Ting Jia; Zhi Zeng; H. Q. Lin (AIP Advances, 2017)
The serial system Srn+1FenO2n+1(n=1,2,3…) with the FeO4 square planar motif exhibits abundant phase transitions under pressure. In this work, we investigate the pressure-induced structural, magnetic and transport transitions in Sr2FeO3 from first-principles. Our results show that the system undergoes a structural transition from Immm to Ammm when the volume decreases by 30%, together with a spin-state transition (SST) from high-spin (S = 2) to intermediate-spin (S = 1), an antiferromagnetic-to-ferromagnetic transition and an insulator-to-metal transition (IMT). Besides, the IMT here is a bandwidth controlled transition, but little influenced by the SST.